Conjunctival-corneal melt in association with carotid artery stenosis - Rosalind MK Stewart (Dove Medical Press, 2008)
Rosalind MK Stewart1, Say Aun Quah1, Dan Q Nguyen2, Stephen B Kaye11Royal Liverpool University Hospital, Liverpool, UK; 2Bristol Eye Hospital, Bristol, UKPurpose: To report a case of severe conjunctival-corneal melt in association with carotid artery stenosis.Methods: Observational case report.Results: A 76-year-old man with a history of bilateral severe carotid artery occlusion and nonarteritic ischemic optic neuropathy developed a spontaneous bulbar conjunctival defect. Despite intensive lubrication, and attempts at surgical closure including an amniotic membrane patch graft, it progressed with subsequent adjacent corneal perforation. Thorough investigations revealed no underlying disease, except markedly delayed episcleral vessel filling on anterior segment fluorescein angiography.Conclusions: Neovascularisation is a known factor in the inhibition of ulceration. In light of the findings in this report, ocular ischemia should be considered as a cause or contributing factor in the differential diagnosis of conjunctival-corneal melt.Keywords: conjunctival melt, corneal melt, ocular ischemia, carotid artery stenosis